A survey on fault-tolerant consensus control of multi-agent systems: trends, methodologies and prospects. Issue 13 (3rd October 2022) - Gao, Chen; He, Xiao; Dong, Hongli; Liu, Hongjian; Lyu, Guangran
Abstract : The consensus control problem of multi-agent systems (MASs) has received an increasing research interest with ever-developing consensus theory. Before it can be widely applied to actual engineering, the consensus theory needs to be improved by addressing some practical problems. One of the key problems is how to ensure the desirable performance of each agent as well as the entire MAS when confronted with faults, which is referred to as the fault-tolerant consensus control (FTCC) issue. In this survey, we review the classic and recent results in the context of FTCC from two aspects, namely, physical security and logical security. In addition, we provide the latest results on FTCC where the physical and logical security are considered simultaneously in a framework. Finally, we outline several potential future research topics on the FTCC issue.